Enron : lessons & recommendations for auditors in Singapore - Ang, Ee Hua (2008)
This paper discusses the lessons that could be learnt from the collapse of Enron in relation to the external auditors and applies them in the context of Singapore. It specifically highlights the three areas: auditor independence, ethics and accounting and auditing standards.